Nanostructured Anti-Glare Coatings for Night Visibility. Issue 1 (February 2021) - Madhusudhana, R; Sushma, K L; Chandra Sekhar, K; Krishnamurthy, L.; Gopalakrishne Urs, R; Sangamesha, M A
Abstract: Anti-glare coatings (AGCs) have progressed into highly effective reflectance and glare minimizing components for several optical and opto-electrical equipment's. The extent in research and development with the contribution of nanotechnology in opto-electronics has improved the AGCs. The present study is related to the composition of a nanostructured antiglare coating. In general, antiglare films have been widely used to deal with glare but this is not proper for an outdoor usage in glasses. Hence, improvement in performance of night-driving glasses is necessary to reduce the negative effects of headlights glare. In this paper nanostructured antiglare coating layers on glass substrate is done using Zirconium Oxide (ZrO2 ). The obtained coatings are highly transparent and reflective in nature. Sol–gel method is adopted for the preparation of gel, dip-coating and spin coating technique was employed to develop coatings on glass substrates. The obtained coatings were further characterized by XRD to analyze the phase crystallinity; SEM was used to determine the surface morphology of the coatings, EDX to estimate the elemental composition of the coatings and UV-vis Spectroscope was used to determine the optical properties.